Analisis Kualitas Pelayanan kepada Pelanggan PDAM Tirta Danau Tempe melalui Pendekatan Quality Function Deployment - Setiani Mutia, Ana (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
This study aims to analyze the service quality of PDAM Tirta Danau Tempe in Wajo Regency using the Quality Function Deployment (QFD) method with the House of Quality (HoQ) approach. The research methods used include qualitative data collection through interviews and observations, and quantitative data through questionnaires filled out by 30 respondents from 650 PDAM customers. Validity and reliability tests were conducted to ensure data consistency, while HoQ analysis was used to link customer desires with the quality of service provided. The results show that the most important service attributes for customers are the PDAM's good reputation, timely office operation time, and effective communication by staff. However, some aspects such as the company's compliance with service promises and the availability of a comfortable waiting room need to be improved. The conclusion of this study is that there is a need to improve service quality through a thorough evaluation of these attributes to increase customer satisfaction and strengthen their loyalty. Technical recommendations include improving employee work ethics, handling customer complaints, and more appropriate employee placement to improve PDAM service performance.